Communication Strategy Of Government Public Relations Depok City In Managing Covid-19 Information During Pandemic On Instagram - Desna Aryana Pratiwi; Amri Dunan (CV. Inara, 2021)
Multiple crises in aspects of life have occurred due to Covid-19. The infodemic on social media has resulted in government agencies needing to carry out optimal management of government communication media, especially social media. Diskominfo Depok has a communication strategy to deal with Covid-19 information on Instagram. Qualitative research methods with a case study approach, Mc.Luhan's Media Ecological Theory and S.W.O.T Analysis in public relations.The results showed that the implementation of persuasive and contributive communication strategies by Diskominfo on Instagram @pemkotdepok to achieve good public communication and realize the vision and mission of Diskominfo as government public relations. The progress of social media Instagram @pemkotdepok is intensively developed as concrete evidence of Mc. Luhan's assumption in Media Ecology Theory